Contribution of nitrogen from sugarcane harvest residues and urea for crop nutrition (Scientia Agricola, 2013)
Sugarcane (Saccharum spp.) harvested without burning provides a substantial amount of remains (trash) on soil profiles which can be decomposed and release nutrients contributing to reduce fertilizer needs. The contribution of nitrogen (N) from sugarcane plant residues and fertilizer in sugarcane nutrition was assessed. Plant cane treatments were micro plots of 15N-labeled urea, sugarcane trash and root system; the last two to simulate the previous crop residues incorporated into the soil after crop renewal. For ratoons, N-ammonium nitrate (N-AN) micro plots, 150 kg ha-1 of N-AN and control (0 kg ha-1) were set up to evaluate the contribution of trash in N supply and quantify the effects of N-fertilizer on N-trash mineralization. The N balances derived from each 15N source were calculated after four crops and resulted in: 15N-urea applied at planting, 31 % was recovered by plant cane, 12 % by the following ratoons, 20 % remained in the soil and 37 % was not found in the soil-system (NOC). For crop residues 15N-trash + roots 26 % was recovered by sugarcane, 51 % remained in soil, and 23 % was NOC. N-fertilizer applied to ratoons nearly doubled the amount of N from green harvest residues recovered by sugarcane; 17 vs. 31 %. Water balances and crop evapotranspiration were correlated with 15N-sources recoveries and cumulative N recovery presented a positive correlation with evapotranspiration (2005 to 2009). The 15N balances indicated that crop residues are supplementary sources of N for sugarcane and may contribute to reduce N fertilizer needs since trash is annually added to the soil.